Traditional reading versus digital reading - Romero, Leda (2014)
This article pretends to be an approach to an academic debate between two scenarios that have risen amongst reading as we know it. With the integration of technological devices as iPads, Kindles, laptops, etc. the objectives, experiences and actors that participate in the reading process are inevitable affected, re-configuring the concept. This is why it is worth to distinguish both scenarios and generate a conversation that lead us to integrate both worlds and make reading a rewarding experience that’s integrated to digital life.